PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 006 TELUK SEJUAH KECAMATAN KELAYANG - Deswita Heni; Hendri Marhadi; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to improved learning outcomes IPS class IV at SDN 006 Teluk Sejuah Kecamatan Kelayang by using model Quantum Teaching. The subjects were students of class IV totaling 17 students. This type of research is a classroom action research (Classroom Actions Research) which comprises two cycles (4 meetings). Based on the survey results revealed that an increase in student learning outcomes. The average value of daily tests before deploying IPS students learning model Quantum Teaching is 68.82 only 7 people who completed (41.18%). At UH 1 first cycle increased to 70.88, rose as much as 2.99% by students who completed 11 votes (64.71%). In the second cycle increases in value as much as 25.31% to 88.82 all students complete (100%). This is supported by the activities of teachers in the first cycle-one meetings to gain success 58.33% with unfavorable category. At the 2nd meeting increased to 70.83% in both categories. In the second cycle-one meetings to acquire 83.33% success with both categories. At the 2nd meeting increased to 91.67% with very good category. As for the activity of students in the first cycle-one meetings to gain success 45.83% with less category. At the 2nd meeting were 62.5% in the category enough. In the second cycle to meeting all first gained 79.17% success with both categories. At the 2nd meeting increased to 87.5% with very good category. Thus, it can be concluded that the application of Quantum Teaching learning model can improve learning outcomes IPS class IV SDN 006 Teluk Sejuah Kecamatan KelayangKeyword: Learning Model of Quantum Teaching , Learning Outcomes IPS